2022
DOI: 10.3389/fimmu.2022.1026475
|View full text |Cite
|
Sign up to set email alerts
|

An update on the use of cryoablation and immunotherapy for breast cancer

Abstract: The use of cryoablation, a minimally-invasive image-guided technique to target and kill cancer cells, continues to gain traction within the medical field and with patients. This includes the use of cryoablation for the treatment of small breast cancers and focal sites of metastatic disease. In comparison to open surgical approaches, length of hospital stay and recovery time are decreased with the use of cryoablation. Research studies have also found that cryoablation may actually enhance tumor susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(40 reference statements)
0
10
0
1
Order By: Relevance
“…Cryoablation protects the integrity of tumour antigens and thus induces strong anti‐tumour immunity 13,18 . Breast cancer patients who received ipilimumab (αCTLA4) and cryoablation demonstrated sustained proliferation of CD4 + and CD8 + T cells 43 . Combination of αPD1 with cryoablation led to anti‐tumour immune responses and delayed tumour growth of distant untreated tumours in a renal cell carcinoma model 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Cryoablation protects the integrity of tumour antigens and thus induces strong anti‐tumour immunity 13,18 . Breast cancer patients who received ipilimumab (αCTLA4) and cryoablation demonstrated sustained proliferation of CD4 + and CD8 + T cells 43 . Combination of αPD1 with cryoablation led to anti‐tumour immune responses and delayed tumour growth of distant untreated tumours in a renal cell carcinoma model 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A freezing agent such as liquid nitrogen is pumped into the cryoprobe to freeze and kill the tumor cells by necrosis or apoptosis. Compared with RFA and MWA, cryoablation is less painful and has the benefit of a faster postoperative recovery [ 78 ]. Cryoablation is a relatively new option in oncotherapy and is most suitable for the treatment of elderly patients with tumors near the skin.…”
Section: Classification and Characteristics Of Tumor Ablation Therapymentioning
confidence: 99%
“…Today, cryosurgery can be monitored by modern imaging for precise and control zone ablation and is widely used in the clinics, showing beneficial responses in skin, liver, breast, renal, and prostate cancer alone or in combination with chemotherapy, immunotherapy (such as immune checkpoint inhibitors), radiotherapy, or embolization. 33 , 34 Furthermore, recent studies performed in mouse models have shown how cryoablation not only destroys neoplastic tissues but can also generate a systemic tumor-specific immune response, enhancing the ability of the immune system to recognize and attack cancer cells both locally and systemically, eradicating micro-metastases. 35 , 36 …”
Section: Therapeutic Application Of Cold In Cancer Treatmentmentioning
confidence: 99%
“… 31 , 33 , 35 , 36 Interestingly, this immune response enhancement upon localized breast cancer cryotherapy has been associated with the abscopal effect that can trigger a systemic immune response that leads to the regression of the distant, untreated tumors. 34 , 35 In other words, the immune system is activated by the localized treatment and starts attacking cancer cells throughout the body. Moreover, freezing temperatures disrupt cells and mitochondrial metabolic functions, triggering Bax proteins and apoptotic pathways.…”
Section: Therapeutic Application Of Cold In Cancer Treatmentmentioning
confidence: 99%